2004
DOI: 10.1016/s0093-691x(03)00226-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of lowered temperatures and media on short-term preservation of zebu (Bos indicus) preantral ovarian follicles

Abstract: Effects of lowered temperatures and media on short-term preservation of zebu (Bos indicus) preantral ovarian folliclesThe maintenance of follicle quality during the transportation of ovaries is essential for the successful cryopreservation and in vitro development of preantral follicles. The objective of this study was to evaluate the effect of cooling ovarian tissue on the conservation of zebu cow preantral follicles. Ovarian pieces were immersed in saline or coconut water (CW) solutions and maintained at 4 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
24
2
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 22 publications
(55 reference statements)
3
24
2
4
Order By: Relevance
“…Similarly, Carrascal et al (2012) found that primordial and transitional follicles are more resistant than primary and secondary follicles to cooling procedures after vitrification. The result disagrees with Lucci et al (2004), who found no differences in cryopreserved ovarian follicles of cattle in the primordial, primary and secondary classes. This greater tolerance of primordial follicles can be explained by several features that make them less vulnerable to cryoinjuries, such as: a small oocyte size, low metabolic rate, stage of the cell cycle, absence of pellucid zone and peripheral cortical granules, and a small amount of intra cytoplasmic lipid droplets (Shaw et al 2000).…”
Section: Experiments Icontrasting
confidence: 96%
See 1 more Smart Citation
“…Similarly, Carrascal et al (2012) found that primordial and transitional follicles are more resistant than primary and secondary follicles to cooling procedures after vitrification. The result disagrees with Lucci et al (2004), who found no differences in cryopreserved ovarian follicles of cattle in the primordial, primary and secondary classes. This greater tolerance of primordial follicles can be explained by several features that make them less vulnerable to cryoinjuries, such as: a small oocyte size, low metabolic rate, stage of the cell cycle, absence of pellucid zone and peripheral cortical granules, and a small amount of intra cytoplasmic lipid droplets (Shaw et al 2000).…”
Section: Experiments Icontrasting
confidence: 96%
“…Similarly, different dimethylsulfoxide concentrations have been successfully used with ovarian tissue fragments of sheep, 3M (Santos et al 2006b), 2.6 M ) and 5M . Lucci et al (2004) evaluated several cryoprotectants: ethylene glycol, propanediol and dimethylsulfoxide (1.5 or 3mol/L) and found more pyknotic nuclear changes in bovine ovarian tissue fragments when using ethyleneglycol than with dimethylsulfoxide. In this study, the concentration of 5mol/L of dimethylsulfoxide showed up effective as intracellular cryoprotectant in the process of vitrification of bovine preantral follicles.…”
Section: Experiments Imentioning
confidence: 99%
“…Generally, one of the key factors in organ preservation is restoration of the ATP concentration in the tissues during preservation [9,21]. It has been shown that maintaining the preservation solution at a low temperature is beneficial for restoring the developmental competence of oocytes obtained from ovaries preserved for a long period of time [2][3][4][5][6][7][8]. Supplementation with an energy substrate is another method of restoring organ activity.…”
Section: Discussionmentioning
confidence: 99%
“…In general, to prevent ischemic injuries, a delicate balance of the energy levels within the ovary during storage is thought to be achieved by two strategies, (1) reducing the activity of energyconsuming processes, and (2) increasing the rate of energy production (via glycolysis). Lowering the temperature of the preservation solution has been used for mammalian ovaries; this method improved the quality of the oocytes obtained from ovaries preserved for a long period of time [2][3][4][5][6][7][8], although preservation of porcine ovaries at 15 C reduced the quality of the oocytes compared with that at 25 C. On the other hand, it has been reported that the glucose level in the tissue and exhaustion of anaerobic glycolysis are essential factors that determine the tolerance limit under ischemic conditions [9]. However, few reports have studied the effect of supplementing ovary preservation solution with an energy substrate on the developmental competence of oocytes collected from ovaries preserved for a long period of times.…”
mentioning
confidence: 99%
“…However, as PBS is a very simple medium comprised of a few constituents, the use of richer substances is suggested for female genetic material preservation. In this context, coconut water based solutions (Cocos nucifera) have proved to be efficient for the transportation of caprine (Silva et al, 2000), ovine (Andrade et al, 2002), and bovine (Lucci et al, 2004) ovaries. Recently, a media based on powdered coconut water (ACP ® , ACP Biotechnology®, Fortaleza, CE, Brazil) has also provided successful preservation of canine PFs in situ .…”
Section: Introductionmentioning
confidence: 99%